Influencia de la comunicación familiar en la conducta delictiva de los adolescentes pertenecientes al programa justicia juvenil restaurativa del ministerio público - la libertad 2014 - Perez Gallardo, Lilia Mariangela (2015)
The research entitled "INFLUENCE OF FAMILY COMMUNICATION IN CRIMINAL CONDUCT OF BELONGING TO TEENS Restorative Justice PROSECUTORS PROGRAM - 2014 FREEDOM" arises from the need to understand the factors that influence teenagers to commit infractions law; considering that the participation of adolescents in criminal acts is growing. As for social factors, the following was considered: origin, risk environment, education, school problems, use of leisure time, risk environment; Risk friends; in the family factor, it was considered: type of family, parenting styles, family relationship, family problems. The research is descriptive; use was made of the methods: inductive -deductivo, analytic-synthetic and statistical; observation guide, interview guide, questionnaire and records: with the techniques of observation, interviews, surveys and data analysis, as was used instruments. The study population constitute 40 adolescents belonging to the Restorative Justice Program of Public Prosecutions - La Libertad. The results confirm that the unlawful behavior of adolescents are related to the social factor and family factor. These factors play an important role in the development of adolescent behavior.